Unequal Gains from Remote Work during COVID-19 between Spouses: Evidence from Longitudinal Data in Singapore - Zeewan Lee; Poh Lin Tan; Jie-Sheng Tan-Soo (ZBW - Leibniz Information Centre for Economics, 2023)
The rise of remote work arrangements under the COVID-19 pandemic has generated important benefits, enhancing worker productivity by providing flexibility and reducing commuting costs. Would such positive labor market outcomes enjoyed equally between spouses? Using a longitudinal dataset of married women and their spouses before, during and after the lockdown in Singapore, we examine the effect of the pandemic and the availability of remote work on the respondents' salary income, while accounting for the moderating roles of gendered differences in time use (e.g., in childcare) and presence of helpers. We find a significant salary income growth among male remote workers, but not among females. While both male and female remote workers experienced an increase in income if they spent less time on household work, women were less likely to face such smaller household responsibilities than men. This study provides empirical evidence that unequal division of household labor leads to unequal gains from remote work.
Additional information: Unequal gains from teleworking during COVID-19 - this project was supported by funding from the Lee Kuan Yew School of Public Policy, National University of Singapore [R-603-000-347-115; A-0003976-00-00; R-603-000-237-133]
Keywords: J16; J24; 330; gender; income; COVID-19; remote work; flexible work; time use